Morvan's syndrome and myasthenia gravis related to familial Mediterranean fever gene mutations. Issue 1 (December 2016) - Koge, Junpei; Hayashi, Shintaro; Murai, Hiroyuki; Yokoyama, Jun; Mizuno, Yuri; Uehara, Taira; Ueda, Naoyasu; Watanabe, Osamu; Takashima, Hiroshi; Kira, Jun-ichi
Abstract Background We present the first case of Morvan's syndrome (MoS) and myasthenia gravis (MG) related to familial Mediterranean fever (FMF) gene mutations. Case presentation A 40-year-old woman with a 1-year history of bilateral ptosis and limb muscle weakness presented to our hospital. She also had memory impairment, insomnia, hyperhidrosis, and muscle twitches. Electromyography confirmed widespread myokymia, and there was evidence of temporal region dysfunction on electroencephalography. Anti-voltage-gated potassium channel complex antibodies and anti-acetylcholine receptor antibodies were both positive. Edrophonium administration was effective for bilateral ptosis and muscle weakness. She and her family experienced self-limiting febrile attacks with arthralgia, which led us to suspect FMF. Genetic analyses revealed compound heterozygous mutations in exon 2 of theMEFV gene (L110P/E148Q). From these findings, a diagnosis of MoS and MG complicated withMEFV gene mutations was made. Intravenous high-dose corticosteroids, plasma exchange, and intravenous immunoglobulin resulted in only transient, limited improvement, and frequent relapses, especially in the myasthenic symptoms. Interleukin (IL)-6, IL-1β, and tumor necrosis factor-α were markedly elevated in the serum, which was considered to be derived from theMEFV mutations and responsible for the resistance to immunotherapy. Conclusion The present case illustrates a possible link between auto-inflammation and auto-antibody-mediated neurological diseases.